Clothes. - Harvey, John. (Montreal : McGill-Queen's University Press, 2008)
Annotation. What shall I wear today? Who shall I be? Whether it's a pair of old jeans, a smart, job-clinching suit or the latest haute couture creation, we know that what we choose to wear each day is an important matter. Whether we are rebels, conservatives or trendsetters, our clothes say something about how we feel and the image we want to present to the world. They reflect our individuality, wealth and position in society. Shell suits, club ties, puffball skirts and cravats: clothes appal, enthral, amuse and confuse. In this fascinating book, John Harvey steals a look inside the modern-day wardrobe to reveal how, by being aware of the role clothes play in our lives, we can come to know and better understand who we are.
Cover; Half Title; Title; Copyright; Dedication; Contents; Acknowledgements; The incident in Stubbylee Park; 1 Why can't we trust our clothes?; 2 On trend, off trend: fashion and freedom; 3 What shall I wear, who shall I be?; 4 Clothes and the body within the clothes; 5 Team colours; 6 Couturiers and objets d'art; Conclusion: dream clothes and future clothes; Further reading; References; Index.
College Audience
Keywords: Clothing and dress; Fashion; Philosophy, Modern -- 20th century; HEALTH & FITNESS -- Beauty & Grooming; Clothing and dress; Fashion; Philosophy, Modern; 1900-1999; Electronic books; Electronic books